2018
DOI: 10.1371/journal.pone.0191134
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the anterior ocular segment biometry with HbA1c level in type 2 diabetes mellitus patients

Abstract: ObjectivesTo compare the anterior ocular segment biometry among Type 2 diabetes mellitus (DM) with no diabetic retinopathy (DR) and non-proliferative diabetic retinopathy (NPDR), and to evaluate the correlation of anterior ocular segment biometry with HbA1c level.MethodsA cross-sectional study was conducted in Hospital Universiti Sains Malaysia, Kelantan from November 2013 till May 2016 among Type 2 DM patients (DM with no DR and DM with NPDR). The patients were evaluated for anterior ocular segment biometry [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 55 publications
(82 reference statements)
1
19
0
1
Order By: Relevance
“…Some previous studies reported an increased CCT in DM patients than non-DM, regardless of retinopathy status. For example, Suraida et al [12] found that there was significant mean difference of CCT between non-DM and DM with nonproliferative diabetic retinopathy (NPDR) or no DR in T2DM patients; the NPDR group showed the highest CCT of 529.26 μ m, then 524.60 μ m for the no DR group, and 493.12 μ m for the non-DM group. It differed from the study by Uzel et al, who found patients with juvenile DM had similar CCT, K1, and K2 compared to age- and sex-matched healthy children, the mean CCT value was 542.95 μ m and 541.38 μ m, respectively [8].…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies reported an increased CCT in DM patients than non-DM, regardless of retinopathy status. For example, Suraida et al [12] found that there was significant mean difference of CCT between non-DM and DM with nonproliferative diabetic retinopathy (NPDR) or no DR in T2DM patients; the NPDR group showed the highest CCT of 529.26 μ m, then 524.60 μ m for the no DR group, and 493.12 μ m for the non-DM group. It differed from the study by Uzel et al, who found patients with juvenile DM had similar CCT, K1, and K2 compared to age- and sex-matched healthy children, the mean CCT value was 542.95 μ m and 541.38 μ m, respectively [8].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies postulate the influence of hyperglycaemia on endothelial dysfunction with consistent stromal hydration and swelling of the cornea [2, 5, 8, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM), one of the most common metabolic disorders worldwide, is associated with many ocular complications. First of all, diabetic retinopathy (DR) affects the retinal vessels and is divided into two main groups, namely, nonproliferative diabetic retinopathy (NPDR) and proliferative diabetic retinopathy (PDR) [1, 2]. Patients with DM are also predisposed to damage of all layers of the cornea.…”
Section: Introductionmentioning
confidence: 99%
“…Recently published research findings on corneal morphology show evidence of greater central corneal thickness (CCT) in patients with T2D [7780]. In studies of corneal thickness in patients with diabetic retinopathy, no statistical differences were found between groups of patients with proliferative retinopathy or nonproliferative retinopathy and those without diabetic retinopathy [8185]. These results indicate that diabetes patients have a significantly thicker CCT, regardless of the state of retinopathy.…”
Section: Diabetes and Corneal Stromamentioning
confidence: 98%